Prolonged hospitalization and readmissions for hyperemesis gravidarum – Associations with personal and family history of nausea - Lindström, Venla S.; Laitinen, Linda M.; Nurmi, J. Miina A.; Koivisto, Mari A.; Polo-Kantola, Päivi (Elsevier BV, 2026)
Objectives: Hyperemesis gravidarum (HG) is characterized by severe nausea and vomiting in pregnancy and often requires hospitalization. Risk factors for severe HG remain poorly investigated. We aimed to identify risk factors for more severe HG, defined by prolonged and recurrent hospitalizations.
Methods: This cross-sectional study included 102 women hospitalized for HG. Data from medical records and questionnaires covered history of motion sickness, nausea related to migraine, and family history of nausea and vomiting in pregnancy (NVP). Women were categorized using three criteria: (1) hospitalization length (≤3 days vs. > 3 days), (2) readmissions (none vs. ≥ 1), and (3) combined HG severity: milder vs. more severe HG (≤3 days and no readmissions vs. > 3 days and ≥ 1 readmission). Logistic regression was adjusted for age, body mass index, parity, and marital status.
Results: Women with more severe HG (longer hospitalizations and readmissions) were hospitalized earlier in pregnancy than those with milder HG (8.0 vs. 10.0 gestational weeks, p = 0.002). After adjustment, readmissions were more common among women with a history of motion sickness (71%) than among those without (49%, p = 0.029). Nausea related to migraine and a family history of NVP showed no association with readmissions. None of the nausea-related factors were associated with longer hospital stays or combined HG severity.
Conclusion: Earlier hospitalization may indicate a more severe HG phenotype, emphasizing the importance of timely recognition and sufficient medical care. Although personal history of nausea and family history of NVP are known HG risk factors in general, they did not strongly predict more severe HG.